Стартовая система термостатирования космического ракетного комплекса на базе фреоновых холодильных машин - Горбенко, Г. А.; Чайка, Д. В.; Иваненко, Н. И. (НТУ "ХПИ", 2008)
Розглянута актуальність розробки сучасних та ефективних стартових систем термостатування ракетно-космічних комплексів. Розглянуті існуючі засоби забезпечення потрібної вологості повітря у стартових системах термостатування. Запропонована принципова схема стартової системи термостатування на базі фреонових холодильних машин із використанням підпорного дроселю.

Actuality of modern high-efficient base thermal control systems development for space rockets is examination. Existance providing methods for humidity control in base thermal control systems for space rockers is submit for consideration. Principle scheme of base thermal control systems for space rockers, with freon refrigerating unit and supporting throttle is propose.
Base thermal control system for space rocket with freon refrigeration unit
Keywords: температурно-влажностные режимы; осушители; точка росы; атмосферный воздух